(untitled) (Altre Modernità, 2010)
This work is a comparative analysis of three films on Barcelona. The movies look like a portrait of the Catalan society of XXI Century and show the relationship among the idea of death and the city in the third millennium, through a code between the filmic language of fiction and documentary. Death appear as part of life, and has several meanings. Different definitions were detected by ’death’: as an event and social and social and anthropological change, natural transformation of neighborhood, city, but also as opportunity to preserve the memory; or is social evil, violence and personal tragedy. The three filmmakers witness the ebb and death of an era in a city, in a Barcelona neighborhood to make way for the future. Art represents a possibility of urban survival. The work investigate relations among transformation, death and society in the three movies. The preservation and maintenance of memory is realized through the eyes of the camera too. The three artists focus their attention in Barcelona, its suburbs and especially in the central neighborhood of Raval, or Barrio Chino", in recent decades of remodeling this part of the city. Their aesthetics could be compared to the one aesthetics of others Spanish artists of XX Century. Development concerning the passage of time in urban areas are interwoven with personal stories that define individual to society today and through chronic feature. Death is also a mutation of a social model of manners, which leaves room for the development of a different society: multi-ethnic and open.